Discussion on Classic Variants of Little Red Riding Hood as an Alternative Activity for Literary Analysis at EFL classroom - Leni Marlina (International Conference on Languages and Arts, 2012)
Fairy tales plays a significant role ‘in the socialization processes of the child who reads them’ through cultural norms represented in them (Kuykendal and Sturm 2007, p.38). One of the popular fairy tales which may structure readers’ imagination is Little Red Riding Hood (LRRH). This fairy tale is very popular as Beckett (2002, p.xv) states that ‘No folk or fairy tales has been so relentlessly reinterpreted, recontextualized, and retold over the centuries as Little Red Riding Hood.’ The tale of LRRH has gone through many adaptations and modifications throughout its history.  Zipes (1993) in his book, The Trials and Tribulations of Little Red Riding Hood, explains in details the numerous classic and modern variants of LRRH.  Through this paper I will discuss how to do an alternative activity for literary analysis at EFL classroom by showing a discussion on three selected classic variants of LRRH in the way how they may reflect the change of childhood concept. These variants are selected from Zipes’ book. They consist of early folktale version, Perrault’s version, and Brothers Grimm’s version.The focus of discussion in this paper is the assumptions about sexuality and childhood in selected versions of classic LRRH. I argue that the issue of sexuality clearly exists in the evolution of selected classic variants of LRRH even though the sexuality details may be much less emphasized because of the change in the conceptions of childhood.The result of literary analysis in this paper concludes that the implied readers of LRRH are positioned to be sympathetic to the young female protagonist who should have been clever enough to encounter the sexuality danger. Key words:Little Red Riding Hood, fairy tales, literary criticism